In Forming Religious Behavior and Entrepreneurship - Abdul Ghofur; Miftakhurozaq Miftakhurozaq; Hendri Maryanto (ISTAWA, 2019)
This research journal aims to find out the implementation of Gusjigang's local wisdom-based character education in shaping religious behavior and entrepreneurship at High School Hasyim Asy'ari 3 and High School Mawaqi'ul Ulum Kudus. This research method is a qualitative study with research subjects as Head of High School Hasyim Asy'ari 3 and High School Mawaqi'ul Ulum Kudus. Data collection techniques using the method of observation, interviews, documentation, data triangulation. Data analysis techniques using the theory of Miles and Huberman then validated the validity with triangulation. This research journal produces a description and analysis: First, the content of the implementation of Gusjigang's local wisdom-based character education in shaping religious behavior and entrepreneurship starts from the formulation of the madrasa curriculum, character component development, applied through learning and character culture of madrasas. Second, the pattern of implementation of character education based on Gusjigang's local wisdom in shaping religious behavior and entrepreneurship by developing the core values of Good Commerce into the character component, implementing them through madrasa cultural activities, self-development and life skills training, then followed up with an internship program. Third, the impact of the implementation of Gusjigang character education in shaping religious behavior and entrepreneurship shows a positive response marked by the emergence of religiosity, independence, creativity, and marketing spirit of students. Jurnal penelitian ini bertujuan untuk mengetahui implementasi pendidikan karakter berbasis kearifan lokal Gusjigang dalam membentuk perilaku keagamaan dan kewirausahaan di SMA Hasyim Asy'ari 3 dan SMA Mawaqi'ul Ulum Kudus. Metode penelitian ini adalah penelitian kualitatif dengan subjek penelitian sebagai Kepala SMA Hasyim Asy'ari 3 dan SMA Mawaqi'ul Ulum Kudus. Teknik pengumpulan data menggunakan metode observasi, wawancara, dokumentasi, triangulasi data. Teknik analisis data menggunakan teori Miles dan Huberman kemudian memvalidasi validitas dengan triangulasi. Jurnal penelitian ini menghasilkan deskripsi dan analisis: Pertama, isi dari implementasi pendidikan karakter berbasis kearifan lokal Gusjigang dalam membentuk perilaku keagamaan dan kewirausahaan dimulai dari perumusan kurikulum madrasah, pengembangan komponen karakter, diterapkan melalui pembelajaran dan budaya karakter madrasah. Kedua, pola penerapan pendidikan karakter berdasarkan kearifan lokal Gusjigang dalam membentuk perilaku keagamaan dan kewirausahaan dengan mengembangkan nilai-nilai inti dari Perdagangan Baik ke dalam komponen karakter, menerapkannya melalui kegiatan budaya madrasah, pengembangan diri dan pelatihan keterampilan hidup, kemudian diikuti dengan program magang. Ketiga, dampak implementasi pendidikan karakter Gusjigang dalam membentuk perilaku keagamaan dan kewirausahaan menunjukkan respons positif yang ditandai dengan munculnya agama, kemandirian, kreativitas, dan semangat pemasaran siswa.